BODY CONDITION SCORE INDUK, BOBOT LAHIR PEDET, DAN BOBOT SAPIH PEDET SAPI BRAHMAN CROSS PADA PETERNAKAN RAKYAT DI KECAMATAN TANJUNGSARI KABUPATEN LAMPUNG SELATAN - Anisa Farhani; Kusuma Adhianto; Akhmad Dakhlan; Sulastri Sulastri (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2021)
This study aimed to evaluate Brahman Cross cow from Indonesia Australia Commercial Cattle Breeding (IACCB) program through the cow Body Condition Score (BCS), calf birth weight, and weaning weight of the Brahman Cross at people farm of “Koperasi Produksi Ternak (KPT) Maju Sejahtera” in Tanjungsari District, South Lampung Regency. This study was conducted in March 2020 using survey method with census data collection of which all the 5 years old Brahman Cross cow at the study location were used in this study. The data consisted of primary and secondary data which was analyzed by descriptive analysis. The results of this research showed that the average score of cow BCS, calf birth weight, and weaning weight were 2,92 ± 0,71, 30,04 ± 3,44 kg, 85,63 ± 11,74 kg, respectively. The conclusion of this research was that the cow BCS, calf birth weight, and weaning weight of Brahman Cross from IACCB program in Tanjungsari District is good enough. Keywords: Birth weight, Body Condition Score (BCS), Brahman Cross, Weaning weight